Analyzing Issue of Organizational Commitment: Determining Mediating Factor of Islamic Work Ethic - AYU SULAINI, JUSOH; Zalinawati, Abdullah; Siti Haryati, Shaikh Ali (2014)
Every employee must give his full commitment to the organization for it is the key to the success of an organization. As a Muslim, the religion factor became the basic guide during work because in Islam, as long as a job is done in a condition whereby that employment that does not contradict with Islam, that job can be regarded as a form of worship (Ibadah). Islam is the comprehensive religious in the world. Islamic cover all the aspects included economics, human behavior (akhlak), management, politic and many more. Islam is the comprehensive religious in the world. Islamic cover all the aspects included economics, human behavior (akhlak), management, politic and many more. One of the named aspect is the Islamic work Ethic. Islamic work ethic is the ethic that is stated in the Quran and Sunnah. The purpose of this research is to find out the influences of Islamic Work Ethic towards various issues of job quality, organizational motivational factors with job commitment among employees in Yayasan Islam Kelantan (YIK). In order to be clear on the issue, Islamic work ethics will be analyzed as a mediator variable. The sampling method used in this study is stratified random sampling in 9 places, including YIK and schools that registered under YIK. Personally administered questionnaires were distributed randomly among teachers and staff in secondary schools and YIK. This study uses SPSS (Scientific Package for Social Sciences). Overall, those specified in Frequencies Distribution, Descriptive Analysis, Reliability Analysis, T-Test, Anova, Correlation Coefficient (Pearson’s)and Regression Analysis. There is a significant difference between the genders and age with the organizational commitment. All the dimensions of independent variables are significantly correlated to the Organizational Commitment. However, the Islamic work ethic is a mediating variable in the relationship between deed and intention and salary with organizational commitment.